[Date Index] [Thread Index] [Author Index]
Re: How to solve an implicit system?
On 21 Feb 05 11:50:42 -0500 (EST), bananalimone wrote: >I've to solve the following (simplificated) system: > >y[t+1]=y[t]+(y[t+1]-y[t])+(z[t+1]-z[t]) >z[t+1]=z[t]+(y[t+1]-y[t])+(z[t+1]-z[t]) > >I would like to choose the iterative way, but I don't know how to >start. Anyway any solution is accepted! > >Please help me. > >\bananalimone after simplifying, this system is actually an explicit, so I suppose either you have made a mistake, or the solution is trivial z(t+1)= z(t) y(t+1)= y(t)